Intraoperative Ketorolac 15 mg Versus 30 mg for Analgesia Following Cesarean Delivery: A Retrospective Study. Issue 3 (September 2021) - Yurashevich, M.; Pedro, C.; Fuller, M.; Habib, A.S.
Abstract : ( Int J Obstet Anesth . 2020;44:116–121) Ketorolac is commonly used to manage postcesarean delivery pain. While the manufacturer recommends an intravenous (IV) dose of 30 mg for adults under age 65, a dose of 15 mg is sometimes used. There is a lack of data on the efficacy, outcomes, or side effects associated with a higher or lower dose. This study was conducted in a center that uses both doses for postcesarean analgesia and aimed to compare analgesic efficacy for each dose. The hypothesis was that the 30 mg dose would be associated with lower opioid use.